2001
DOI: 10.1161/01.cir.103.18.2296
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia-Reperfusion of Rat Myocardium Activates Nuclear Factor-κB and Induces Neutrophil Infiltration Via Lipopolysaccharide-Induced CXC Chemokine

Abstract: Background-Mechanisms by which neutrophils are attracted to the myocardium in ischemia/reperfusion are not fully defined. Lipopolysaccharide-induced CXC chemokine (LIX), cytokine-induced neutrophil chemoattractant (KC), and macrophage inflammatory protein-2 (MIP-2) are rodent chemokines with potent neutrophil-chemotactic activity. The goals of the present study were to evaluate the roles of these chemokines in a rat model of ischemia/reperfusion and to examine the mechanisms of chemokine induction by oxidative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
137
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(146 citation statements)
references
References 33 publications
9
137
0
Order By: Relevance
“…were not significantly modulated in any of the treatment groups, CXCL5 (LIX), another potent neutrophil chemoattractant (34,35), was significantly reduced by the IL-17A-specific Ab to concentrations similar to those of control mice. Abs specific for IL-17F or IL-22 did not alter CXCL5 concentrations.…”
Section: Th17 Cells Induce Neutrophilia In the Airways That Is Dependmentioning
confidence: 90%
“…were not significantly modulated in any of the treatment groups, CXCL5 (LIX), another potent neutrophil chemoattractant (34,35), was significantly reduced by the IL-17A-specific Ab to concentrations similar to those of control mice. Abs specific for IL-17F or IL-22 did not alter CXCL5 concentrations.…”
Section: Th17 Cells Induce Neutrophilia In the Airways That Is Dependmentioning
confidence: 90%
“…29 Chronic exposure of proinflammatory cytokines can shift the ratio of transcriptionally active heterodimers to the transcriptionally inactive p50 homodimers, which can act as negative feedback mechanism to prevent excessive production of proinflammatory proteins and may thereby account for the increased expression of proinflammatory proteins in the p50 KO. However, because those factors aggravate the ischemic response in other models, 30 they cannot account for cardioprotection in p50 KOs.…”
Section: Discussionmentioning
confidence: 99%
“…In rodents several ELR positive CXC chemokines, including GRO-α/KC, Macrophage Inflammatory Protein (MIP)-2 and LipopolysaccharideInduced CXC chemokine (LIX), induce neutrophil chemotaxis and activation through binding to their main receptor, CXCR2. Experiments in a rat model of infarction demonstrated that, although KC and MIP-2 are upregulated in the injured heart, neutrophil recruitment in reperfused rat infarcts appeared to be mainly due to expression of LIX [107]. Deficiency of CXCR2, the main receptor for the ELR-containing CXC chemokines, resulted in significantly decreased inflammatory leukocyte recruitment in murine infarcts, suggesting a crucial role for these chemokines in inflammatory cell infiltration [108].…”
Section: Chemokines In Healing Infarctionmentioning
confidence: 99%